The Impact of Digital Capability and Business Synergy on Digital Transformation - Tengku Kespandiar; Silvia Ekasari; Ferdi Antonio; Heny Hidayati; Musdirwan (Indonesian Journal Economic Review (IJER), 2026)
This study examines the influence of digital capabilities and business synergy on digital transformation in higher education institutions facing rapid technological change. Universities are increasingly expected to adapt by strengthening their ability to use digital technologies while maintaining effective coordination across organizational units. Digital capabilities reflect the skills, knowledge, and readiness of institutions in utilizing technology, while business synergy refers to the alignment and collaboration among internal functions to support common goals. A total of ninety respondents from several universities were selected through purposive sampling, ensuring their relevance to digital practices and institutional development. The data were processed using Smart Partial Least Squares (Smart PLS) to evaluate the structural model and test the relationships between variables. The findings show that digital capabilities have a positive and significant effect on digital transformation. Business synergy also demonstrates a significant influence, indicating that coordinated efforts across departments support smoother implementation of digital initiatives. These results indicate that university performance in the digital era depends on the ability to strengthen technological competence and maintain strong internal collaboration. Institutions that are able to integrate both aspects tend to achieve more effective and sustainable transformation outcomes.